The Myth Of The Sea For The Bajo People In The Novel Mata Dan Manusia Laut By Okky Madasari - Maemunah, Siti; Teguh Supriyanto, RM.; Setyaningsih, Nas Haryati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The novel Mata dan Manusia Laut by Okky Madasari is a literary work as a form of culture that describes the life of the Bajo people, especially the Sama village. The people still hold fast and believe in the myths that exist in the sea they live. Based on this statement, this study aimed to find the myths that are built in the plot, characters, and setting of the story. This study used an objective approach with Levi-Strauss' semiotic structuralism theory. The data of this research was a text that contained elements of plot, characters, and setting of the story. The data source of this research was the novel Mata dan Manusia Laut by Okky Madasari. The results showed that the novel Mata dan Manusia Laut by Okky Madasari contained a sea myth that was built on elements of plot, character, and story setting. (1) The storyline of the novel was divided into five episodes and there were 18 mythemes from each episode. (2) The myth was built into several characters, those were the characters of Bambulo, Lummu, the Masalembo Residents (Sam, Ship Captain, Aldio, Mama Lia), and RORO. These characters were related to each other regarding the existence of a sea myth in the novel. (3) The setting of the story described the Atoll and Masalembo which had a mystery.